2011
DOI: 10.1016/j.molcel.2011.04.020
|View full text |Cite
|
Sign up to set email alerts
|

A SIRT1-LSD1 Corepressor Complex Regulates Notch Target Gene Expression and Development

Abstract: Summary Epigenetic regulation of gene expression by histone-modifying co-repressor complexes is central to normal animal development. The NAD+-dependent deacetylase and gene repressor SIRT1 removes histone H4K16 acetylation marks and facilitates heterochromatin formation. However, the mechanistic contribution of SIRT1 to epigenetic regulation at euchromatic loci and whether it acts in concert with other chromatin-modifying activities to control developmental gene expression programs remain unclear. We describe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
167
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 183 publications
(181 citation statements)
references
References 67 publications
13
167
1
Order By: Relevance
“…Indeed, KDM1A depletion in mice impairs neuronal migration [35]. Consistent with these data, KDM1A interacts during Drosophila development with the histone deacetylase SIRT1 to negatively regulate Notch target gene expression by modifying histone modifications [36].…”
Section: Kdm1a and Cellular Differentiationsupporting
confidence: 53%
“…Indeed, KDM1A depletion in mice impairs neuronal migration [35]. Consistent with these data, KDM1A interacts during Drosophila development with the histone deacetylase SIRT1 to negatively regulate Notch target gene expression by modifying histone modifications [36].…”
Section: Kdm1a and Cellular Differentiationsupporting
confidence: 53%
“…Moreover, in a more recent paper, besides the Notch1 degradation by Sirt1-sustained deacetylation, Notch1 target gene expression was driven by the repressory action of Sirt1/LSD1 complex deacetylating and demethylating chromatin. (Mulligan et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that removal of RBPJ/Su(H) in the absence of NICD results in the transient activation (derepression) of some target genes (Morel and Schweisguth 2000;Koelzer and Klein 2003;Mulligan et al 2011;Yatim et al 2012). Our observation that RBPJ occupancy is strongly reduced at the inducible sites under Notch-off conditions prompted us to measure directly the repressive function of endogenous RBPJ in primary myogenic cells.…”
Section: Active Repression By Rbpj Does Not Occur On a Subset Of Its mentioning
confidence: 94%